2018
DOI: 10.1080/08958378.2018.1474976
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginine dimethylaminohydrolase (DDAH) overexpression enhances wound repair in airway epithelial cells exposed to agricultural organic dust

Abstract: Preserving the NO signal through endogenous inhibition of asymmetric dimethylarginine enhances wound repair even in the presence of dust exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…The damage resulting from DDAH activity can lead to an increased ADMA concentration and a series of reactions, such as severe inflammation and oxidative stress, whereas overexpression of DDAH1 could reduce injury. Chandra et al demonstrated that DDAH1 overexpression could enhance wound repair in agricultural organic dust-treated airway epithelial cells [ 39 ]. Similar results were shown by Kinker et al who found that DDAH1 expression declined in the lung tissue following house dust mite exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The damage resulting from DDAH activity can lead to an increased ADMA concentration and a series of reactions, such as severe inflammation and oxidative stress, whereas overexpression of DDAH1 could reduce injury. Chandra et al demonstrated that DDAH1 overexpression could enhance wound repair in agricultural organic dust-treated airway epithelial cells [ 39 ]. Similar results were shown by Kinker et al who found that DDAH1 expression declined in the lung tissue following house dust mite exposure.…”
Section: Discussionmentioning
confidence: 99%
“…During the normal protein cycle, ADMA is formed enzymatically from the methylation of arginine remnants through the activity of redox-sensitive S-adenosylmethionine-dependent protein arginine N-methyltransferases and metabolized to citrulline by dimethylarginine dimethylaminohydrolase (DDAH) [ 22 ]. ADMA levels reported enhancing during induction of gastric injury with ethanol, indomethacin, cold-stress, and H. pylori [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[19]. ADMA выступает в качестве посредника окислительного стресса с помощью подавления eNOS и разобщения путей синтеза NO [20], увеличивая экспрессию воспалительных генов. Выявлено, что в постковидном периоде у пациентов с МС наиболее выраженные (р<0,001) связи между увеличением в сыворотке периферической крови sLIF и уровнями условных вазопрессоров ADMA и SDMA со вторичным снижением вазорелаксанта eNOS, а также повышением функциональных показателей ОПСС и СПВкф.…”
Section: результатыunclassified